2021
DOI: 10.3390/w13162140
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Assessment and Factor Analysis of Water Related Environmental Risk to Cities in the Yangtze River Economic Belt

Abstract: With rapid development of the economy and urbanization, water-related environmental risk in urban areas has increased and hindered social-economic development and ecological protection. The assessment of water-related environmental risk is of vital importance to the sustainable development of the Yangtze River Economic Belt (YREB). This study constructed a comprehensive assessment index system for water-related environmental risks from three perspectives: the hazards posed by risk sources, the effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A reasonable industrial structure can improve the economic benefits of the city, develop the regional social economy, and then provide a firm economic base in order to strengthen the city to withstand external shocks. Nonetheless, our study found that the industrial structure between cities along the YREB's lower reaches is required to be optimized, and TI's development needs to continue to increase (Cui et al, 2021). Secondly, education investment symbols the development potential of the city from the perspective of social development (Yang et al, 2021a), and wage income indicates the development status of the city.…”
Section: Fig 8 Spatial Differentiation Of Ur Along the Yreb's Lower Reachesmentioning
confidence: 83%
See 1 more Smart Citation
“…A reasonable industrial structure can improve the economic benefits of the city, develop the regional social economy, and then provide a firm economic base in order to strengthen the city to withstand external shocks. Nonetheless, our study found that the industrial structure between cities along the YREB's lower reaches is required to be optimized, and TI's development needs to continue to increase (Cui et al, 2021). Secondly, education investment symbols the development potential of the city from the perspective of social development (Yang et al, 2021a), and wage income indicates the development status of the city.…”
Section: Fig 8 Spatial Differentiation Of Ur Along the Yreb's Lower Reachesmentioning
confidence: 83%
“…There are more and more researches used different methods to find the driving factors of UR. Some scholars use spatial measurement models (Zhang et al, 2019), DPSIR model (Drive-Pressure-State-Impact-Response) (Zhao et al, 2021), Obstacle model (Cui et al, 2021) and so on to discuss the driving factors of UR. However, the spatial measurement model mainly calculates the spatial dependence through the impact of the behavior of adjacent areas on the central areas and then judges the driving factors.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical difference in the same index is positively related to the amount of information it contains. The greater the numerical difference, the more information it reflects, the greater the role of the index in the comprehensive evaluation, and the higher its weight [19][20][21][22][23]. The entropy method only depends on the degree of dispersion of the data itself, which can effectively avoid the impact of human or subjective factors on each evaluation index and make the evaluation results more objective and effective.…”
Section: Entropy Weight Methodsmentioning
confidence: 99%